SCARAB : development of a rugged, low cost, inspection-class robotic platform - Mathew, Thomas J (Department of Mechanical Engineering, 2015)
This dissertation details the design and development of a prototype of a new robotic platform designed to carry a variety of sensors into environments that are too dangerous or confined for human workers, and forms part of a series of three concurrent M.Sc(Eng) dissertations which will integrate into a complete system. Ultimately this platform will be controlled and transported by the man-wearable harness and control station developed by W.K. Fong, and will gather data using the sensor payloads designed by G. Knox. Each dissertation, however, has independently quantifiable goals and results. An important application area for such a system is Urban Search and Rescue (USAR): the field of work concerned with the discovery, extrication, and treatment of survivors trapped in collapsed structures. These typically occur as a result of terrorist attacks, natural disasters, or engineering failure. Human workers, often assisted by dogs, are trained in this work but the danger of the working environments make USAR a key area where the use of robotic assistance can make a massive difference in helping to save lives - both those of rescuees and rescuers. A body of existing work, both in the commercial and academic spheres, has been done in this regard, and as a result there is much to be learned from the experiences of others. The history of robot-assisted USAR work, as well as the existing robots available, is surveyed and critically analysed. Significant challenges are noted: existing systems frequently lack sufficient mobility, are too large, difficult to transport and deploy, difficult to use, and very costly. Their cost has affected the prevalence of their use both as a barrier to acquisition but also during their use; robot operators frequently have their decisions constrained by the financial risk of losing or damaging a robot. Accordingly, it is proposed to develop a small, rugged, low-cost inspection-class robot that can be quickly and easily deployed in a variety of scenarios. This development work is covered in three sections; the mechanical and industrial design of the platform, its design, manufacture and assembly are considered first. This is followed by a description of the electrical and electronic systems needed to power and control the robot as it conducts inspections in challenging terrain. To protect the robot from damage in this terrain, impact-absorbing wheels are developed. The test-driven iterative design approach followed, as well as the equipment and methods used therein, constitute a large portion of this dissertation and are detailed in their own chapter which can be read as a sub-project within the main project. The finished prototype is tested against the developed specifications, and from these results conclusions are drawn and recommendations for future work made.